RANCANG BANGUN ISLAM NUSANTARA - Rumadi Ahmad (Universitas Islam Negeri Fatmawati Sukarno, 2015)
This article discusses the design of Islam Nusantara. This essay reveal about what, why, foundation and discussion constellation Islam Nusantara. The word “Islam archipelago” can bring a lot of interpretations, perspectives, even imagination. Imagination wrong about Islam archipelago could lead to mistakes that delegitimize the meaning of the word Islam archipelago. Assumed, Islam Nusantara has the character of Islamfriendly, anti-radical, inclusive and tolerant not “Islamic Arab” is always conflict with fellow Islamic and civil war. Islam Islam archipelago is full of manners, full of manners and tolerance.